Financial Management of Public Service Bodies in State Universities: Juridical Analysis of Fees for the Development of Independent Path New Student Institutions - Arazid, Arazid; Sugiyono, Heru; Thohari, Ahmad Ahsin (PT. Riset Press International, 2025)
This study investigates the financial management of Public Service Agencies (BLU) within Indonesian state universities, focusing on the unauthorized imposition of institutional development fees (SPI/IPI) on independent pathway students at Udayana University, resulting in significant State financial losses. Employing a normative juridical methodology, the research analyzes regulatory frameworks, institutional accountability, and the legal implications of fee structures that contravene Ministry of Finance regulations (PMK No. 51/2015 and PMK No. 95/2020). Findings reveal systemic non-compliance in fee determination, where SPI/IPI charges were applied without legal authorization, bypassing mandated tariff protocols. The study identifies critical lapses in oversight, including the rector's failure to align fee policies with national financial regulations and the misuse of BLU flexibility, which enabled the diversion of funds into non-transparent banking practices. The case underscores the vulnerability of BLU's financial autonomy to mismanagement and corruption, particularly in the absence of robust accountability mechanisms. Recommendations emphasize the urgent need for legal reforms to enhance transparency, strengthen auditing processes, and clarify punitive measures for violations. This research contributes to the discourse on public financial governance in higher education, advocating for institutional reforms to prevent future fiscal mismanagement and uphold the integrity of State’s resources.